PENGARUH SENAM LOW IMPACT TERHADAP TEKANAN DARAH PRA LANSIA DENGAN HIPERTENSI DI PUSKESMAS SAIL KOTA PEKANBARU - Siska Mulyani; Apriyanto Apriyanto; Sri Yanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Hypertension is one of the highest causes of death in people in the world. This disease is call silent killer. The prevalence of hypertension has reached 31.7% of the population in Indonesia. it increase because many factors such as genetics, less of physical activity and smoking. The purpose of this study was to see the effect of low impact exercise on pre-blood pressure in elderly with hypertension. This research was conducted on 12 respondents in Puskesmas Sail Pekanbaru.with bivariate. analysis this research is a quantitative with a quasi experimental design